Efforts To Improve Student Understanding On The Basic Competency Of Making Adjustment Journal Through Working Papers - Sinta Kania Novita (Indonesian Journal of Education Teaching and Learning (IJETL), 2022)
The purpose of this study is to improve the understanding of learning Accounting in class students XII IPS 5 SMA Negeri 1 Talaga, Majalengka Regency for the academic year 2021/2022 with the application of Direct Instruction learning for the Basic Competence of Journaling Adjustment through working paper media. This study uses a Research approach Class Actions. The results showed that the application of the Direct learning model Instructions on Basic Competencies Making Adjusting Journals through working papers can improve the understanding of learning Accounting for students of class XII IPS 5 SMA Negeri 1 Talaga, Majalengka Regency for the academic year 2021/2022. This is reflected in some indicators are as follows: (1) Students who are active during apperception show an increase from 72.73% in the first cycle to 79.8% in the second cycle. (2) Students who are active during ongoing learning showed an increase from 75.76% in the first cycle to 81.82% in cycle II. (3) The level of understanding and accuracy of the explanation of the journal making process adjustments observed during the group discussion process and the presentation of the results of the discussion through the presentation showed an increase from 76.77% in the first cycle to 85.86% in the second cycle. (4) Increased mastery of student learning outcomes from 75.76% in the first cycle to 84.85% in the cycle II.